STRATEGI DAKWAH NURUDDIN ZANKI PADA MASA KEKHALIFAHAN DINASTI FATIMIYAH - Rachman, Anggi Dwi; Fajar, M. Samson; Rohman, Fathur (DECODING: Jurnal Mahasiswa KPI, 2021)
The strategy carried out by Nuruddin Zanki is truly extraordinary in order to restore Islamic values in the midst of society. The leaders of their subordinates are demanded that Shari'ah be enforced in every area they lead, justice is created in every line and against the Shia Ismailimadhhab. It all deserves to be an example for preachers that defending the religion of Allah SWT requires a strategy of da'wah and extraordinary struggles.The research that the author uses is descriptive analysis method, with library research, in this study it is described that NuruddinZanki'sDa'wah Strategy is extraordinary, so that with his maximum efforts, Allah SWT wants the unity of the people to return and the collapse of the Fatimid dynasty with the teachings of Shia.The conclusion of this study is that the Strategy in Preaching is very important, especially to deal with the problems of the people and the Shiites. We leave the results to Allah SWT.